STRATEGY TO INCREASE USER SATISFACTION OF PUBLIC SERVICES IN THE EDUCATIONAL PRINCIPAL DATA SECTION (DAPODIK) OF THE EDUCATION SERVICE AND CULTURE OF MEDAN CITY - Herlin Ruliana S; Anizar; Vivi Gusrini Rahmadan P (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research was investigated to see how much influence the strategy of increasing public service user satisfaction has in the basic education data section (dapodik) of the Medan City Education and Culture Office. This research was conducted using descriptive research and a qualitative approach. The results of the qualitative research were described in the form of words. and language by utilizing various natural methods, research focus is used to limit the scope of the problem so that the research process is not too broad, good research must be supported by valid and accurate data. This data can be obtained from appropriate sources and is appropriate to the problem being studied, Data collection techniques are carried out using appropriate data collection instruments. The research results show that the Dapodik service of the Medan City Education and Culture Service is generally quite good and satisfies service users. Even though it can be said to be quite good, there are still a number of crucial aspects that need to be improved. There are several factors that influence service user satisfaction in the Dapodik section of the Medan City Education and Culture Service. There were at least 6 internal supporting factors and 3 external supporting factors found, and the position of the Dapodik section of the Medan City Education and Culture Service in the SWOT quadrant was found to be between "Weakness" and Opportunity. The WO strategy is the most appropriate to be implemented in the Dapodik section of the Medan City Education and Culture Service.